Ответ:
Объяснение:
![image](https://tex.z-dn.net/?f=%5Cfrac%7Bc%7D%7B4%7D%20-%20%5Cfrac%7Bd%7D%7B12%7D%20%3D%20%5Cfrac%7B3c%20-%20d%7D%7B12%7D%5C%5C%20%20%3C%2Fp%3E%3Cp%3E%5Cfrac%7B3%7D%7B2x%7D%20-%20%5Cfrac%7B2%7D%7B3x%7D%20%3D%20%5Cfrac%7B3%2A3-2%2A2%7D%7B6x%7D%20%3D%20%5Cfrac%7B5%7D%7B6x%7D%5C%5C%20%3C%2Fp%3E%3Cp%3E%20%5Cfrac%7B17y%7D%7B24c%7D%20-%20%5Cfrac%7B25y%7D%7B36c%7D%20%3D%20%5Cfrac%7B17y%2A%203%20-%2025y%2A2%7D%7B72c%7D%20%3D%20%5Cfrac%7By%7D%7B72c%7D%20%5C%5C)
\frac{3}{2x} - \frac{2}{3x} = \frac{3*3-2*2}{6x} = \frac{5}{6x}\\
\frac{17y}{24c} - \frac{25y}{36c} = \frac{17y* 3 - 25y*2}{72c} = \frac{y}{72c} \\" alt="\frac{c}{4} - \frac{d}{12} = \frac{3c - d}{12}\\
\frac{3}{2x} - \frac{2}{3x} = \frac{3*3-2*2}{6x} = \frac{5}{6x}\\
\frac{17y}{24c} - \frac{25y}{36c} = \frac{17y* 3 - 25y*2}{72c} = \frac{y}{72c} \\" align="absmiddle" class="latex-formula">